Annotation of the Asian Citrus Psyllid Genome Reveals a Reduced Innate Immune System - Arp, Alex P.; Hunter, Wayne B.; Pelz-Stelinski, Kirsten S. (Frontiers in Physiology, 2016)
Citrus production worldwide is currently facing significant losses due to citrus greening disease, also known as Huanglongbing. The citrus greening bacteria, Candidatus Liberibacter asiaticus (CLas), is a persistent propagative pathogen transmitted by the Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Liviidae). Hemipterans characterized to date lack a number of insect immune genes, including those associated with the Imd pathway targeting Gram-negative bacteria. The D. citri draft genome was used to characterize the immune defense genes present in D. citri. Predicted mRNAs identified by screening the published D. citri annotated draft genome were manually searched using a custom database of immune genes from previously annotated insect genomes. Toll and JAK/STAT pathways, general defense genes Dual oxidase, Nitric oxide synthase, prophenoloxidase, and cellular immune defense genes were present in D. citri. In contrast, D. citri lacked genes for the Imd pathway, most antimicrobial peptides, 1,3-β-glucan recognition proteins (GNBPs), and complete peptidoglycan recognition proteins. These data suggest that D. citri has a reduced immune capability similar to that observed in A. pisum, P. humanus, and R. prolixus. The absence of immune system genes from the D. citri genome may facilitate CLas infections, and is possibly compensated for by their relationship with their microbial endosymbionts.